STRATEGI INOVATIF DALAM PEMBELAJARAN THAHARAH DI MI PIAT TANJUNG SETEKO - Nuril Pitriyati; Dwi Noviani; Imam Nasruddin; Dewi Purbasari (Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2022)
The quality of the learning process and good learning outcomes is the key to the success of an educator in delivering material. The importance of various skills that must be owned by a student, made researchers moved to conduct this research. The purpose of this study is to find out and describe the meaning of learning strategies, to find out the types of learning strategies and to find out how to develop innovative strategies in thaharah (cleanliness) learning. The method used in this study is to use a qualitative approach to the type of library research. Sources of data for this research come from articles, journals, books, and several other scientific works. The results of this study are by using innovative learning strategies the learning atmosphere becomes fun and can make students motivated and enthusiastic about participating in learning. There are several types of learning strategies including: expository learning strategies, inquiry learning strategies and cooperative learning strategies. This innovative learning includes uncleanness, hadast (large, medium, small) as well as procedures for ablution and tayammum. Innovative learning strategies used in thaharah learning can use games, show videos and practice. This can make students understand more about what is being studied.